SISTEM PENUNJANG KEPUTUSAN PENERIMAAN KARYAWAN BARU MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) PADA PT CRESTEC INDONESIA CIKARANG - Rizky Ayu Saputri; Angely Noviana Sianturi; Siti Mutmainnah; Eka Rini Yulia (JURNAL INFORMATIKA DAN KOMPUTER, 2022)
Employees are the most essential part of the company. To obtain qualified and qualified employees, companies usually hold a selection process. The selection process is carried out before the employee is declared accepted. In the process of recruiting prospective employees, PT. Crestec Indonesia is still using the manual method. A large number of applicants makes it very difficult for HRD to choose the right employee candidates who meet the criteria to be accepted to work in the company. The absence of a computerized system and the right method is one of the inhibiting factors in making decisions to accept new employees in the company. The purpose of the selection of recruitment is to obtain the right and qualified employees so that employees can work optimally in the company. To improve the new employee recruitment system that is faster and more precise, a web-based computerized system is needed by applying the SAW (Simple Additive Weighting) method which can facilitate HRD in the decision-making process of hiring new employees. The results of the Decision Support System by applying the SAW method are getting a ranking process so that it becomes the best recommendation in accepting new employees.